An Investigation on Jawi CAPTCHA Based Security for Login Authentication and Authorization: Is It an Alternative Solution? - Sakinah Ali Pitchay; Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan; Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng; Suhaimi, NNM (Int Assoc Engineers-Iaeng, 2024)
Authentication plays a significant role in computer security to validate human users. CAPTCHA is one of human interaction proof test to verify whether user is a human or a computer program. It has become a very popular security mechanism used to prevent any automated abuse of online services which is intended for human user. The test usually is provided in the authentication phase where the user will be directed to the next page if they are authorized. From the login site, an attacker creates a program exploiting the username and password to get into a website. Recently, there are a lot of different types of CAPTCHA available on the internet. However, most of them have been successfully attacked by automated programs. Thus, this paper investigates existing related works on CAPTCHA which focus on login authentication and authorization by proposes a different approach using Jawi script. Based on investigations of the systematic review and preliminary findings, it shows that this is the first work that proposed using a different script and possible future directions for producing more reliable human/computer distinguishers. Future works will develop an alternative and stronger CAPTCHA to prevent breaking cyber-attack such as dictionary attack while maintaining ease of implementation on website and ease of use for human by reducing the difficulties on reading the CAPTCHA.